Citizenship behavior and effectiveness in temporary organizations - Braun, T.; Ferreira, A.; Sydow, J. (International Journal of Project Management, 2013)
Studying temporary organizations from a behavioral perspective, we theorize how Organizational Citizenship Behavior (OCB) as a form of cooperative effort may enhance the effectiveness of this type of organization, rendering the temporary organizations vital, even beyond their termination. Building upon such a perspective, a quantitative, cross-sectional study was conducted, with 247 project managers and workers participating. Principal component analysis and hierarchical regression analysis were performed. The results reveal that OCB not only facilitates meeting the “iron triangle” (time, budget, quality) of project management but also improves the relationship quality among individual actors beyond the termination of projects. This relationship is partially moderated by project duration. The implications of the findings are discussed.